2012
DOI: 10.3402/jev.v1i0.18389
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mRNA and microRNA in human mast cell‐derived exosomes and their transfer to other mast cells and blood CD34 progenitor cells

Abstract: BackgroundExosomes are nanosized vesicles of endocytic origin that are released into the extracellular environment by many different cells. It has been shown that exosomes from various cellular origins contain a substantial amount of RNA (mainly mRNA and microRNA). More importantly, exosomes are capable of delivering their RNA content to target cells, which is a novel way of cell-to-cell communication. The aim of this study was to evaluate whether exosomal shuttle RNA could play a role in the communication bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
149
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 36 publications
11
149
0
4
Order By: Relevance
“…It is known that miR-210 is upregulated during hypoxia, stimulates angiogenesis, induces proliferation, and decreases apoptosis [9]. In an allergic context, miR-210 expression has been shown to increase in mouse lymph nodes and T regulatory cells following dermal chemical sensitization [10], and miR-210 is upregulated in exosomes released by the HMC-1 cell line [11]. …”
Section: Resultsmentioning
confidence: 99%
“…It is known that miR-210 is upregulated during hypoxia, stimulates angiogenesis, induces proliferation, and decreases apoptosis [9]. In an allergic context, miR-210 expression has been shown to increase in mouse lymph nodes and T regulatory cells following dermal chemical sensitization [10], and miR-210 is upregulated in exosomes released by the HMC-1 cell line [11]. …”
Section: Resultsmentioning
confidence: 99%
“…Exosomes containing mRNAs can be transferred and influence the translational profile of recipient cells and tumour progression [47,72,76,77]. For example, Skog et al showed that by incorporating mRNA for a reporter oncogenic protein EGFRvIII into EVs, these transcripts (3426 transcripts present at different levels in exosomes and their donor cells) could be delivered to, and translated by recipient cells [77].…”
Section: Mrnamentioning
confidence: 98%
“…Exosomes contain a cornucopia of lipids, proteins, mRNA, and microRNA species and represent a novel mechanism of cell-cell communications, including exchange of genetic information (van Niel et al, 2006;Record et al, 2011). Mast cell exosomes can directly activate other cells (Skokos et al, 2001;Al-Nedawi et al, 2005), transfer mRNA and selective species of microRNA to other cells (Ekstrom et al, 2012), as well as several proteins (Valadi et al, 2007). Mast cell exosomes released during stress responses may be able to protect other cells from similar injury (Eldh et al, 2010), an effect likely mediated by transferred RNA.…”
Section: Mast Cell and Basophil Mediatorsmentioning
confidence: 97%